The design of restorative outdoor environments for cancer patients - Abdul Shukor, Shureen Faris; Shafee, Norsuriani (UPM-MAKNA Cancer Research Laboratory, Institute of Bioscience, 2014)
A cancer diagnosis brings with it multiple psychological crises, including loss of control, loss of self-efficacy, isolation, decrease self-esteem and, grief. Several studies have presented evidences that actual or stimulated view of nature can produce substantial restoration from psychological stress within a few minutes. A research also found that patients recovered faster and with fewer strong medications when windows faced a natural view rather than a brick wall. This paper will discuss how outdoor spaces with restorative qualities may provide an environment conducive to stress reduction, mental repose, emotional recovery and, the enhancement of mental and physical energy. Literature concerning the design recommendations for outdoor environments for cancer patients are identified and analysed. Among the design considerations include implementing interactive garden features, spaces for different type of users (adult, children, staff and visitors) and, easy access. A case study using Post Occupancy Evaluation at the National Cancer Institute in Malaysia is being carried out in order to investigate the possibilities of having a restorative outdoor environment in a local context. The knowledge gathered from this study may contribute to the body of knowledge in designing outdoor environments for cancer treatment centres in Malaysia.